Cost assessment of multi-tenancy for a 5G broadband network in a dense urban area. Issue 2 (5th March 2020) - Rendon Schneir, Juan; Konstantinou, Konstantinos; Bradford, Julie; Zimmermann, Gerd; Droste, Heinz; Canto Palancar, Rafael; Ajibulu, Ade
Abstract : Purpose: 5G systems will enable an improved transmission performance and the delivery of advanced communication services. To meet the expected requirements, operators will need to invest in network modernisation, with the radio access network being the most expensive network component. One possible way for operators to reduce this investment would be via sharing of resources by means of a multi-tenancy concept. This implies that a mobile service provider may use the common infrastructure of one or various infrastructure providers, whereby it provides services to multiple tenants. This paper aims to study the expected cost savings in terms of capital expenditures (CAPEX) and operational expenditures (OPEX) that can be achieved when using a cloudified 5G multi-tenant network. Design/methodology/approach: A cost model was used. The study period is 2020-2030 and the study area consists of three local districts in central London, UK. Findings: This paper describes that the total cost reduction achieved when using multi-tenancy for a 5G broadband network in comparison with the case where operators make the investment independently ranges from 5.2% to 15.5%. Research limitations/implications: Further research is needed to assess the cost implications of network sharing for 5G on a regional or nationwide basis. Originality/value: Very little quantitative research about the cost implications of network sharing under 5G networks has been published so far. This paper sheds light on the economic benefits of multi-tenancy in a 5G broadband network.